Effect of reaction styles theory-based interventions on relieving fatigue of patients with systemic lupus erythematosus (基于反应风格理论的干预方案在缓解系统性红斑狼疮患者疲劳中的应用研究) - LI Yuwei (李雨蔚); SONG Weiting (宋炜婷); WANG Sa (王飒); QIAO Caicai (乔彩彩); LIANG Lifen (梁丽芬); MIAO Huali (苗华丽) (中西医结合护理)
Objective This study aims to investigate the effect of interventions based on response styles theory on relieving fatigue in patients with systemic lupus erythematosus. Methods A total of 72 SLE patients admitted to the Rheumatology and Immunology Department of a tertiary hospital in Shanxi Province from March 2024 to September 2024 were selected and divided into a control group of 36 patients (receiving routine nursing interventions) and an experimental group of 36 patients (receiving routine interventions and interventions based on response styles theory). The Multidimensional Fatigue Inventory(MFI-20) scores and lupus quality of life scale (Lupus-QoL)scores of the two groups of patients were compared. Results After the intervention, the MFI-20 scores of the experimental group were significantly lower than those of the control group, and the Lupus-QoL scores of the experimental group were significantly higher than those of the control group, and the differences were statistically significant (P＜0. 001). Conclusion This study suggests that intervention programs based on response styles theory can help relieve fatigue of patients with systemic lupus erythematosus, and enhance their quality of life. (目的 本研究旨在讨论基于反应风格理论的干预方案对改善系统性红斑狼疮(SLE)患者疲劳的效果。方法 选择2024年3月—9月山西省某三甲医院风湿免疫科住院部收治的SLE患者72例, 采用随机数字表法将患者分为对照组和试验组, 各36例。对照组接受常规护理干预, 试验组在常规护理的基础上, 基于反应风格理论实施干预方案。比较两组患者的多维疲劳量表(MFI-20)评分和狼疮生活质量量表(Lupus-QoL)评分。结果 干预后, 试验组MFI-20评分较对照组降低, 差异有统计学意义(P＜0. 001)。干预后, 试验组Lupus-QoL评分较对照组升高明显, 差异有统计学意义(P＜0. 001)。结论 基于反应风格理论的干预方案有助于改善SLE患者的疲劳状况, 提升患者的生活质量, 具有较高的临床价值。)